Strategies for Effective Management of Intellectually Disabled Patients on the Psychiatric Inpatient Unit - Gonzalez, Luisa; Nwugbana, Ifeoma; Patel, Rahulkumar; Lombardo, Marissa; Korenis, Panagiota (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
The management of aggressive behavior remains a fundamental challenge when working on a psychiatric inpatient service. The task becomes far more daunting when the patient presents not only with mental illness but also has an intellectual disability (ID) or impulse control disorder (IC). Intellectual Disability is defined as “the impairment of general mental abilities that impact adaptive functioning in three domains: conceptual, social and practical.” Impulse control disorder, is defined as “a psychiatric disorder characterized by impulsivity- the failure to resist a temptation, urge or impulse that may harm oneself or others” [1]. Those with ID and or IC may present with varying degrees of impairment and social functioning. Numerous studies have identified an association with ID and psychiatric co-morbidities including: bipolar disorder, impulse control disorder, psychosis and depression. Due to budgetary cuts and the precipitous decline in available residential placements, inpatient psychiatric services are faced with the dilemma of managing these exceptionally complicated patients. While numerous studies have examined the utility of psychotropic medication to aid in the management of these patients, convincing evidence concerning the use of psychiatric medication in the management of this patient population remains elusive [2]. Therefore, this paper aims to explore the treatment strategies available to the multidisciplinary team on the inpatient service. Ultimately, future investigations will be necessary to better understand how to optimize the inpatient management of this complex patient population.